The Effectivenes of Model Eliciting Activities on Increasing Mathematical Creative Thinking - Ayuningtyas, Winda; Triyono, Ageng; Marhaeni, Nafida Hetty; Ramos, Sarah Vegas (IndoMath: Indonesia Mathematics Education, 2023)
Learning mathematics in Indonesia has not had a significant effect on improving students' creative thinking abilities. It is hoped that the Model Elicting Activities (MEAs) trial can be an alternative solution to this problem. So the first objective of the study was to find out whether MEAs learning had a better effect on improving students' creative thinking skills compared to conventional learning models. The second research objective is to determine the level of effectiveness of implementing the MEAs learning itself. The research objectives were achieved using a quasi-experimental study method with the pretest-post-test non-equivalent group design. The research subjects were class VII students of SMP L'Pina, East Jakarta, consisting of 25 students from the experimental class and 25 students from the control class. The research instrument is a test of creative thinking skills. Data on test results were analyzed using the t-test. The results of the data analysis concluded that: (1) MEAs learning has a better influence on students' creative thinking abilities than conventional learning models, and; (2) MEAs learning can significantly improve students' creative thinking skills.